1992
DOI: 10.1007/bf00868136
|View full text |Cite
|
Sign up to set email alerts
|

Active and inactive renin after exercise

Abstract: The effects of graded exercise on plasma concentrations of active and inactive renin were studied in seven healthy men. Exercise was performed on a cycle ergometer at four different exercise intensities (corresponding to 30%, 50%, 80% and 87% of VO2max) for 10 min each. Concentrations of active renin and total renin after activation by trypsin were measured by direct immunoradiometric assay. Non-trypsin-activated renin concentration (inactive) was obtained by subtraction. Active renin concentrations at 30%, 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…As for the mechanism behind the anti-hypertensive effect, Kiyonaga et al reported that an increase in nitric oxide and prostaglandin E due to exercise acts directly on vascular smooth muscle to relax blood vessels and reduce peripheral vascular resistance to lower the BP [31]. It has also been shown that a decrease in sympathetic nerve activity due to a decrease in blood catecholamines at rest leads to relaxation of peripheral blood vessels and a decrease in cardiac output [32].…”
Section: Interpretationsmentioning
confidence: 99%
“…As for the mechanism behind the anti-hypertensive effect, Kiyonaga et al reported that an increase in nitric oxide and prostaglandin E due to exercise acts directly on vascular smooth muscle to relax blood vessels and reduce peripheral vascular resistance to lower the BP [31]. It has also been shown that a decrease in sympathetic nerve activity due to a decrease in blood catecholamines at rest leads to relaxation of peripheral blood vessels and a decrease in cardiac output [32].…”
Section: Interpretationsmentioning
confidence: 99%
“…Además, los receptores β de las células granulares aumentan de manera directa la secreción de renina ante la presencia estimuladora de los neurotransmisores simpáticos, en especial de la noradrenalina (16,17). Están bien documentados la hiperactividad simpática y el incremento de la concentración plasmática de la noradrenalina y la adrenalina durante la actividad física (18)(19)(20).…”
Section: Palabras Claveunclassified